“Beyond the pale of mercy”: Victorian penal culture, police court missionaries, and the origins of probation in England - Auerbach, Sascha (Cambridge University Press, 2015)
One of the most striking changes in the penal culture of fin-de-siècle Europe was England's reform of adjudication and punishment. In this “de-moralization of criminality,” the system began to shed its punitive sentencing, which often saw minor offenders imprisoned with hard labor for weeks or months, to adopt a more moderate system of penalties. These concrete changes were intertwined with a broader shift in British criminological thinking from a “classical” view to a “positivist” one. The former held offending to be a rational, individual choice that required severe deterrents, whereas the latter saw criminality as a product of harsh economic and social conditions. This shift in dominant understandings of criminality prompted reformers, judicial officials, police, and policymakers to refocus on the causes of crime and its prevention, the offender as a subject, and the potential for treatment and rehabilitation through state intervention. A central practice of the resultant “penal-welfare complex” was supervised probation as a substitute for imprisonment. Scholars of penal reform have argued that the passage of the Probation of Offenders Act 1907, which initiated the professionalization of the probation service, was a key moment in this transition. With it, such arguments hold, England took a substantial step from having a discretionary, moralized criminal justice system toward having a standardized, bureaucratic one.